2019
DOI: 10.18332/tid/102673
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of cancers attributable to smoking in Korea, 2014

Abstract: INTRODUCTIONAssociations between smoking, cancer and mortality are well established. Although cancer mortality rates have decreased in recent years, the economic burden of smoking-related cancers continues to increase. This study investigates the economic costs of cancers related to smoking in Korea in 2014.METHODSCancer patients were identified through National Health Insurance Services medical claims with ICD-10 cancer codes. We multiplied the costs by the population attributable fraction for each type of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Regarding the method for indirect cost estimation, our approach was similar to a previous study in South Korea in 2019. That study found that the indirect cost was approximately 77.91% of the total cost, and future income lost accounted for the largest percentage of the cost components [32]. In Iran, researchers found that it accounted for 55% of the total cost (not including productivity loss or job loss) [19].…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the method for indirect cost estimation, our approach was similar to a previous study in South Korea in 2019. That study found that the indirect cost was approximately 77.91% of the total cost, and future income lost accounted for the largest percentage of the cost components [32]. In Iran, researchers found that it accounted for 55% of the total cost (not including productivity loss or job loss) [19].…”
Section: Discussionmentioning
confidence: 97%
“…A typical threshold for cost-effectiveness of interventions is $50 000 (approximately €46 000) per quality-adjusted life-year, but this threshold has been criticized as being too low [18]. Novel cancer treatments are often considered cost-effective despite much less favorable ratios [19][20][21][22][23][24][25] (see Table S3 for examples). Although estimates for cancer mortality reduction did not consider tumor stage, site, molecular subtypes, etc., our results suggest that daily vitamin D supplementation in the German population aged 50 years and older for reducing cancer mortality would be overall cost-saving, or at least highly cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…The GDP lost i.e. 0.41% of Pakistan due to smoking attributed illnesses is higher than reported from Iran (0.26%) 16 , Korea (0.2%) 17 and Sri Lanka (0.15%) 18 . But it is less than Thailand and Uganda where the smoking attributed burden accounts for 0.7% and 0.5% of the country GDP respectively 19 20 .…”
Section: Discussionmentioning
confidence: 71%